$\sqrt {(3 + \sqrt 5 )} - \sqrt {(2 + \sqrt 3 )} = $

  • A

    $\sqrt {(5/2)} + \sqrt {(3/2)} $

  • B

    $\sqrt {(5/2)} - \sqrt {(3/2)} $

  • C

    $\sqrt {(5/2)} - \sqrt {(1/2)} $

  • D

    $\sqrt {(3/2)} - \sqrt {(1/2)} $

Similar Questions

The number of integers $q , 1 \leq q \leq 2021$, such that $\sqrt{ q }$ is rational, and $\frac{1}{ q }$ has a terminating decimal expansion, is

  • [KVPY 2021]

The equation $\sqrt {(x + 1)} - \sqrt {(x - 1)} = \sqrt {(4x - 1)} $, $x \in R$ has

If $x = {{\sqrt 5 + \sqrt 2 } \over {\sqrt 5 - \sqrt 2 }},y = {{\sqrt 5 - \sqrt 2 } \over {\sqrt 5 + \sqrt 2 }},$ then $3{x^2} + 4xy - 3{y^2} = $

The value of $\sqrt {[12 - \sqrt {(68 + 48\sqrt 2 )} ]} = $

If $x = {2^{1/3}} - {2^{ - 1/3}},$ then $2{x^3} + 6x = $